Antioxidant capacity of matcha in syrnyky technology: improving the quality of fermented milk dishes - Kuzmin, Dmytro; Suiarko, Borys; Levandovskyi, Leonid; Kuzmin, Oleg (My University, 2025)
The article presents the results of comparative studies on the antioxidant capacity and sensory profile of green tea and matcha, followed by their adaptation to syrnyky (cottage cheese pancakes) technology. It was found that water-alcohol infusion of matcha exhibits the highest antioxidant activity and the most favorable sensory characteristics: intense green color, pronounced herbal aroma, and a well-balanced astringent-sweet taste with a creamy aftertaste. Based on the obtained data, an improved syrnyky formulation was developed with the addition of 1-3% matcha powder, which enhanced their quality by increasing nutritional and biological value and improving organoleptic properties. The study confirms the potential of matcha as a functional ingredient that enhances the appeal of modern Ukrainian cuisine. У статті представлено результати порівняльних досліджень антиоксидантної здатності та сенсорного профілю чаю зеленого та матча, при подальшій їх адаптації до технології сирників. Встановлено, що водно-спиртовий настій матча має найвищу антиоксидантну активність і найкращі сенсорні характеристики: насичений зелений колір, виразний трав’яний аромат та збалансований терпко-солодкий смак із вершковим післясмаком. На основі отриманих даних розроблено удосконалену рецептуру сирників із додаванням 1–3% порошку матча, що дозволило покращити їх якість завдяки покращенню харчової та біологічної цінності та поліпшенню органолептичних показників. Дослідження підтверджує перспективність використання матча як функціонального інгредієнта, що підвищує привабливість страв сучасної української кухні.
Keywords: кафедра технології ресторанної і аюрведичної продукції; green tea; antioxidant capacity; sensory evaluation; water-alcohol infusions; fermented milk dishes; syrnyky; cottage cheese pancakes; modern Ukrainian cuisine; foodservice establishments; матча; чай зелений; антиоксидантна здатність; сенсорна оцінка; водно-спиртові настої; страви з кисломолочного сиру; сирники; сучасна українська кухня; заклади ресторанного господарства